Longitudinal photovoice examination of workplace experiences for Congolese refugee women in the United States - Shannon McMorrow; Jyotika Saksena (Dialogues in Health)
Refugees fleeing the Democratic Republic of Congo are vulnerable to health and social inequities. Women from the DRC are at unique risk within the social and cultural milieu of the U.S., but there is insufficient evidence to inform tailored programs and policies for this population. This article describes results from a longitudinal, qualitative Photovoice study with women refugees from the DRC between 2016 and 2023. Participatory analysis with participant co-researchers and inductive manual analysis revealed four themes illustrating experiences with employment and the workplace: job (in)security, discrimination, injuries, and workplace potential. Evidence from this study demonstrates the need for more intentional, tailored public health and social service interventions centering on the workplace for Congolese refugee women resettled in the U.S. The federal policy pushes refugees toward early self-sufficiency. Our findings suggest this is problematic as it negatively impacts language acquisition, which in turn creates a ripple effect of negative outcomes, including insufficient access to jobs offering a living wage, limited access to jobs with health insurance, and exposure to jobs with high risk of injury or social settings enhancing discrimination. These experiences can be further exacerbated for women refugees from Africa standing at the intersection of race, gender, and refugee status. Study results also show opportunities for the workplace to be an outlet for positive health impacts and advocacy for social justice for this population and potentially other refugee groups that are marginalized in the U.S.